THE EFFECTIVITY OF THE APPLICATION TECHNICAL PROBING PROMPTING ON STORY PROBLEMS IS REVIEWED FROM MATHEMATICAL CREATIVE THINKING SKILLS TO HIGH SCHOOL STUDENT - Dede Suhendar ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
This article present the results of research in the form of effectiveness using probing prompting techniques and experimental research methods with desain pre experimental : one-shot case study design by  purposive sampling conducted on class X students in the 2018/2019 academic year on mathematical questions in the form of story problems. While the objectives of this study include exposing the effectiveness of mathematical creative thinking abilities of students using probing promting techniques, obtaining a number of descriptions of students problems in the process of creative thinking in mathematical questions form of story matter. Based on data analysis the results of the study showed that the percentage of students who have good mathematical creative thinking skills is less than 60%, so the probing prompting technique is not effective in terms of mathematical creative thinking abilities students.